Pelatihan Ketepatan Empati dengan Menggunakan Model Experiential Learning untuk Siswa SMK Jurusan Keperawatan - Septiana, Nila Zaimatus (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2016)
Empathic accuracy is a person's ability to properly understand the thoughts, feelings and intentions or desires of others. High empathic accuracy allows a person to succeed in various fields. Improving empathic accuracy can be done by providing a range of experiences. One of them is experiential learning. The study aims to test the effectiveness of empathy training accuracy by using experiential models for vocational students, Department of Nursing. The methods used in this study were within the group or individual design and research design used was equivalent time series. Wilcoxon signed rank test was used to analyze the data. The results showed that empathic accuracy training using experiential learning models effectively improvesempathic accuracy of vocational students of Department of Nursing.